2011
DOI: 10.3390/molecules16064728
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and Phenolic Content of Caesalpinia pyramidalis Tul. and Sapium glandulosum (L.) Morong from Northeastern Brazil

Abstract: The aims of this study were to quantify the phenolic content and evaluate the antioxidant potential of extracts from the bark and leaves of C. pyramidalis and S. glandulosum. The total phenolic content (TPC) and total tannin content (TTC) were determined using the Folin-Ciocalteu method, and the total flavonoids content (TFC) was measured via complexation with aluminum chloride. The antioxidant activity was evaluated with DPPH (2.2-diphenyl-1-picrylhydrazyl) and FIC (ferrous ion chelating) assays. The TPC rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
4
13
0
Order By: Relevance
“…In the 6 h protocol, only the high dose of EECp (400 mg/kg) was able to decrease MDA formation after 6 h of pancreatitis induction, but maintained this effect until 24 h after CBDO, which was also observed for two administrations of this ethanol extract. This indicates that EECp provided protection against the lipoperoxidation caused by CBDO, an observation that completely agrees with prior findings that the aqueous (Alviano et al, 2008) or ethanolic (Silva et al, 2011) extracts of C. pyramidalis inner bark induce 2,2-diphenyl-1-picrylhydrazyl (DPPH) consumption in vitro, a widely used antioxidant assay. In agreement with the antioxidant and anti-inflammatory effects of EECp, our results show that the production of NO was decreased in animals treated with this extract, as NO metabolites were detected at lower concentrations in the serum of these animals.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the 6 h protocol, only the high dose of EECp (400 mg/kg) was able to decrease MDA formation after 6 h of pancreatitis induction, but maintained this effect until 24 h after CBDO, which was also observed for two administrations of this ethanol extract. This indicates that EECp provided protection against the lipoperoxidation caused by CBDO, an observation that completely agrees with prior findings that the aqueous (Alviano et al, 2008) or ethanolic (Silva et al, 2011) extracts of C. pyramidalis inner bark induce 2,2-diphenyl-1-picrylhydrazyl (DPPH) consumption in vitro, a widely used antioxidant assay. In agreement with the antioxidant and anti-inflammatory effects of EECp, our results show that the production of NO was decreased in animals treated with this extract, as NO metabolites were detected at lower concentrations in the serum of these animals.…”
Section: Discussionsupporting
confidence: 86%
“…In this way, there are a number of compounds described in this plant, and many of them are phenolic compounds, especially flavonoids (Mendes et al, 2000;Bahia et al, 2005Bahia et al, , 2010Silva et al, 2011). The components of EECp are still unknown, and the present study has suggested that rutin -but not apigenin (found in the leaves of Caesapinia pyramidalis; Bahia et al, 2005), quercetin or baicalein-is likely to be present in EECp.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our result (1 mg/mL) was similar to the value reported by Muñoz-Ortiz et al (2011) [31], who found an IC 50 of 1.30 mg/mL for leaves of Caesalpinia pluviosa , which were collected in Ballivian Province and were deposited in the National Herbarium of Bolivia in La Paz (number of vouchers: VM6). However, the IC 50 value for Caesalpinia bonducella was much smaller at IC 50 = 74.73 μg/mL [32], as for the bark of C. pyramidalis IC 50 = 16.98 ± 1.34 μg/mL, which was incorporated in the Herbarium UFP Geraldo Mariz, Department of Botany, Federal University of Penambuco, with the number 60.195 [33], indicating more active antioxidants in the bark of this plant. The FRAP value is a measure of the capacity of the antioxidant to reduce ferric (III) to ferrous (II) ions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the species Sapium glandulosum, only one study that investigated the content of phenolic compounds and the antioxidant activity of ethanol extracts of the bark and leaves was found (Silva et al, 2011). The aim of this study was the investigation of the latex from plants of the family Euphorbiaceae concerning proteinase activity.…”
Section: Introductionmentioning
confidence: 99%